2015
DOI: 10.1177/1559325815588507
|View full text |Cite
|
Sign up to set email alerts
|

Local Tumor Control and Normal Tissue Toxicity of Pulsed Low-Dose Rate Radiotherapy for Recurrent Lung Cancer

Abstract: Objectives:This study investigates (1) local tumor control and (2) normal tissue toxicity of pulsed low-dose rate radiotherapy (PLDR) for recurrent lung cancer.Methods:For study 1, nude mice were implanted with A549 tumors and divided into the following 3 groups: (1) control (n = 10), (2) conventional radiotherapy (RT; n = 10), and (3) PLDR (n = 10). Tumor-bearing mice received 2 Gy daily dose for 2 consecutive days. Weekly magnetic resonance imaging was used for tumor growth monitoring. For study 2, 20 mice r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…In accordance with what has been previously published we observed histopathological signs of reduced toxicity in mice following PLDR when compared with equivalent doses of CRT 5 ( Fig. 1).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In accordance with what has been previously published we observed histopathological signs of reduced toxicity in mice following PLDR when compared with equivalent doses of CRT 5 ( Fig. 1).…”
Section: Resultssupporting
confidence: 81%
“…Male balb/c mice were subjected to the same total physical doses of whole-body radiation using 2 different radiation delivery protocols 5 according to an approved Fox Chase Cancer Center and Temple Health Institutional Animal Care and Use Committee protocol. Conventional radiotherapy (CRT) was delivered as a single dose of 8 Gy whereas PLDR involved delivery in 40 fractions of 0.2 Gy separated by 3 minutes.…”
Section: Mice and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…PLDR not only exerts increased tumor control capacity but also favors normal tissue sparing and the preservation of vascular network. In the lung cancer murine model, Zhang et al found that PLDR could control tumors as effectively as the conventional radiotherapy but results in much less normal tissue toxicities than the conventional radiotherapy [5] . The preclinical study demonstrated that the combination of PLDR and temozolomide was associated with increased vascularization and fewer degenerating neurons compared with standard fractionated treatment plus temozolomide [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, spreading the total doses into short, low-dose pulses been shown to effectively limit tissue toxicity and minimize complications. 1,2 Although PLDR has been validated in pre-clinical and clinical studies, the molecular basis of reduced necrosis and preserved normal tissue integrity has remained unclear.…”
mentioning
confidence: 99%